High refractive index silicone gels for simultaneous total internal reflection fluorescence and traction force microscopy of adherent cells. - Edgar Gutierrez; Eugene Tkachenko; Achim Besser; Prithu Sundd; Klaus Ley; Gaudenz Danuser; Mark H Ginsberg; Alex Groisman (PLoS ONE)
Substrate rigidity profoundly impacts cellular behaviors such as migration, gene expression, and cell fate. Total Internal Reflection Fluorescence (TIRF) microscopy enables selective visualization of the dynamics of substrate adhesions, vesicle trafficking, and biochemical signaling at the cell-substrate interface. Here we apply high-refractive-index silicone gels to perform TIRF microscopy on substrates with a wide range of physiological elastic moduli and simultaneously measure traction forces exerted by cells on the substrate.